Effect of β-Hydroxy-β-methyl butyrate (HMB) on innate immune response in different Atlantic salmon families - Mostazo, Miriam Guadalupe Contreras, 1991- (2013)
The aim of this project was to investigate the effect of β-Hydroxy-β-methyl butyrate (HMB) on the expression of antimicrobial peptides (AMP) and inducible nitric oxide synthase (iNOS) in Atlantic salmon (Salmo salar), administering it in the diet and water. We studied two different families of S. salar and fish were divided into four groups. Fish were sampled over a period of three weeks. The expression of cathelicidin-2 (asCATH2), Hepcidin-1 and iNOS, both important components for the first line of immune defenses, was measured in gill, kidney, spleen and heart tissues. Up-regulation of asCATH2 and iNOS was observed after HMB treatment with increases of expression at different times. In addition, the responses varied throughout days but the variation between families was not significant. Hepcidin-1 expression rather than being enhanced, was in some cases, down-regulated, nevertheless, in one of the two families it was significant enhanced during the last days-post-induction. The study provides us with a powerful molecular tool to evaluate the innate immunity system of different salmon families. Further investigations will be undertaken to confirm whether higher AMP gene expression, or other defense mechanisms of innate immunity, are valuable as a natural protection against common diseases.